The Influence of Good Corporate Governance, Fraudulent Financial Statements, and Company Size on Company Value - Danul Ilham; Arif Bijaksana Z; M. Farhan Rusmawan (Budapest International Research and Critics University, 2022)
This study to show the influence of Good Corporate Governance, Fraudulent Financial Statements, and Firm Size to Firm Value. The sample used in this study is based on the Property, Real Estate, and Building Construction sectors included in the DES index during the 2017-2019 period. By using purposive sampling method obtained sample based on annual report as many as 108 companies that have been in selection and meet the criteria. In the multiple regression test, the results of this study indicate that firm size has a significant negative effect on firm value, while Good Corporate Governance and Fraudulent Financial Statements have no significant effect on firm value.